Physical and Mechanical Properties of Teak (Tectona grandis L.fil.) Thermo-Plywood from Plantations in Lao P.D.R (Global Journal of Science Frontier Research, 2022)
The aim of this research to investigated physical and mechanical properties of thermal plywood of PF adhesive. Physical property focused on density, water absorption and swelling. And mechanical property was MOR, MOE, shearing strength and hardness. The Teak veneer was the main raw material the size was 2 mm in thickness, and 400 mm in width and length. The veneer was divided into five groups as were control, thermos-veneer, at 180°C, at 200°C, 220°C and 240°C and 4 min, 8 min and 12 min, the spread 150 g/m2 and five layers. Plywood products used PF adhesive products were cool pressing in 10 min and hot pressing in 15 min. density test followed with AS/ANZ 2098.7, 2012, WA and swelling thickness were followed ASTM D 3502-76, The dimension sample design was 10x25x300 mm for MOR and MOE, 10x50x100 mm for shearing strength and 10x50x50 for harness and testing by Fast Test software. Data analyses were One-way ANOVA and multiple linear regression. As the result, the density of thermal treatment was decreased density of teak plywood. A control was significant different on thermal treatment of different level of temperature and length of time the control was no significant different.
Keywords: thermo; plywood; density; absorption; swelling; MOR; MOE; shearing; hardness